The impact of economic development on water pollution: trends and policy actions in Malaysia - Muyibi, Suleyman Aremu; Ambali, Abdul Rauf; Eissa, Garout Suleyman (Springer, 2008)
The paper examines the impact of development activities on water pollution in Malaysia. Hence, the main objective of this paper is not just to examine the trends of development-induced water pollution around the region of the country but to know where the problems are and the policy measures taken by the government. It evaluates the probable causative relationship between problems introduced due to technology employed in water pollution control and governmental policy measures. It examines the relationship between development indicators as sources of pollution and polluted rivers over a period of 12 years. The findings of the paper have shown that despite the policy enforcement actions against the identified sources of water pollution, all the three development indicators (chosen based on those identified sources) still accounted for high percentage of river pollution in Malaysia. The findings of the paper were used to identify the central fact of the location of the problem. Some crucial conclusions of where the problems likely to be, as reflected in the findings, are: (a) the issue of interactive-effects between pollutants that many policy-makers are not aware of. This is when policy measures concentrate only on one source of water pollution; (b) the enforcement strength and/or effectiveness of policy measures themselves; (c) financial constraints to invest in appropriate technology especially sewerage systems for controlling human source of water pollution in the country; as well as those confronting small polluting industries (d) finally, lack of cooperation between government and private business firms to comply with regulatory policies for water pollution control.